(untitled) (Bangladesh Journal of Botany, 2024)
The functional properties and mineral nutrients of eleven rice cultivars were investigated. Among the cultivars, Mapillai samba, Arupadham kuruvai, and Karuppu kavuni recorded the presence of higher levels of carbohydrate (67.88mg/100g, 67.47mg/100g and 62.30mg/100g, respectively). Higher levels of fibre of 3.27mg/100g, 2.61 mg/100g and 2.36mg/100g were recorded in Kalabath, Poonkar and Sigappu kavuni, respectively. Higher level of protein content of 15.39mg/100g, 10.80mg/100g and 9.61mg/100g, were recorded in Illupaipoo samba, Thooyamalli and Poonkar, respectively. Interestingly, Kalabath recorded more nitrogen (2.52mg/100g), Mappillai samba recorded more iron (301.70ppm) and manganese (23.02ppm), Arupadahm kuruvai recorded more phosphorus (0.37%) and magnesium (0.98%), Sugappu kavuni recorded more copper (20.26ppm), Karunguruvai recorded more potassium (0.41%) and zinc (40.98ppm). The findings suggested that conventional rice varieties with enhanced functional attributes could support the agricultural community by improving the farming economy while also increasing the health advantages for consumers. Bangladesh J. Bot. 53(4): 931-937, 2024 (December)